Of feathers and tapes: corporeality and experimentation in hybrid environments (Orfeu, 2025)
This text investigates the intersections between body, technology, and sound creation in the piece Have You Ever Seen a Bird Die? (2024), for viola, voice, and tape. Through an artistic-phenomenological approach, it explores the creative process as part of a doctoral research on the presence and corporeality of the performer in hybrid contexts. Divided into four sections, the article contextualizes the composition, analyzes its experimental impulses and poetic references (Costa, Zumthor, Caesar, Merleau-Ponty), and reflects on the compositional processes in light of the instrumentality of each sonic layer. Improvisation, chronicle, and natural sounds are articulated within a poetics that challenges boundaries between spoken and sung, acoustic and electronic. The piece proposes an embodied listening, serving as an invitation to continue artistic investigations on the body as a creative and mediating axis.
Keywords: musical experimentalism; hybridism; viola; tape; voice